Application of Marketing Mix to Improve Consumer Purchasing Decisions on Culinary in The Old Market - Sugandha Sugandha; Fidellis Wato Tholok; Suhendar Janamarta (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
The purpose of this study was to determine the implementation of the Marketing Mix Strategy (Product, Price, Place and Promotion) of Tangerang Old Market Culinary in Increasing Consumer Purchase Interest partially (alone) or simultaneously (together). The research was conducted by distributing questionnaires. , while the research method using Simple Random Sampling. The independent variables in this study are price, location, promotion and service, while the dependent variable in this study is the decision to stay. The data collection method was used by distributing questionnaires directly to the Tangerang Old Market Culinary Consumers. The analytical method used in this research is the analysis of the coefficient of determination, multiple regression analysis of the F test and the t test, using SPSS Version 25.00 which is based on data from 100 Culinary Consumers at the Old Market Tangerang. positive and significant (product t-count value is 6369. > ttable 1.985 and .0000 <0.05 to (Consumer Purchase Interest) At Tangerang Old Market, Price Variable (X2) partially has a positive and significant effect (t-value calculated price is 3559. > ttable 1.985 and. Tangerang , Promotional Variable (X4) partially positive and significant effect (t value of Promotion 4.648. > ttable 1.985 d an .0000 < 0.05 with respect to (Consumer Purchase Interest) at the Tangerang Old Market, and for the F test results obtained results for the calculated F value of 178,855 with a significance value of 0.000 so that the calculated F value > F table or 178,855 > 2.70 or the level of significance (sig) 0.000 <0.05, it can be concluded that there is a simultaneous (together) effect between product, price, place, promotion on consumer buying interest in Tangerang Old Marketand the adjusted R2 value in this study means that the variance in consumer buying interest can be explained by Promotion, Place, Product, Price through the model of .883% and the remaining 11.7% comes from other variables outside of promotion, place, product and price variables. Or in other words, the amount of contribution / contribution of .883 to Consumer Purchase Interest is 88.3%, the remaining 11.7% comes from other variables outside the variables of Promotion, Place, Product, Price